Effect of macronutrients and iron upon the growth and mineral composition of castor bean (Ricinus Communis L.) cultivated in nutrient solution - Iturrieta Rojas, Aída; Neptune, A. M. Louis (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1971)
This work was accomplished with the aim of studying the effects of macronutrients and iron on the growth and chemical composition of the Castor Bean (Ricinus Communis L.) cultivated in nutritive solution. Castor bean seedlings were cultivated during 2 months in complete solution and afterwards were transferred to nutritive solutions with and without the presence of macronutrients and iron (micronutrient). After 2 months of cultivation in deficient solutions, symptoms of lack of N, P, K, Ca, Mg, S and Fe were found and described in this work. As soon as symptoms of deficiency appeared, the plants were harvested and divided in the following fractions: root, old stem, (the portion marked at the time of application of the deficient solution), new stem (the portion grown above the mark), old petioles, new petioles, old leaves, new leaves and fruits. With respect to the development of the plants the following measurements were taken: height, stem diameter, length of central "lobulo" taken from the center of the leaf. Each one of the fractions was also weighed. The N, P, K, Ca, Mg, S and Fe macronutrients concentrations were determined from the old and new leaves and from the total plants. The quantities in mg of each one of these macronutrients absorved by the plant were calculated.